Exploring Shariah Governance Practices In Islamic Co-operatives In Malaysia - Muhammad Iqmal Hisham Kamaruddin; Supiah Salleh; Zurina Shafii; Mustafa Mohd Hanefah; Nurazalia Zakaria (EconJournals, 2024)
Indexed by Scopus